Weeds occurrence in areas submitted to distinct winter crops - Concenço,G. (2012)
In the Western Region of Brazil, it is usual to have two agricultural harvests in the same cropping season. Usually the first crop is soybean, followed by corn. In areas where corn is not planted due to a delayed harvest of soybean, farmers generally do not use winter crops. For these areas, the planting of winter oilseed crops aiming at the production of bio-fuels is one of the best alternatives; in addition, this would help in reducing the occurrence of weed species at the following summer crop. This study aimed to assessing the weed community in distinct winter crops post soybean crop, in terms of species composition, level of infestation and severity of occurrence. The following treatments were evaluated: agriculture under a no-till system with winter fallow, winter oilseed crops (crambe, radish, rapeseed) with no-till agriculture in the summer, and agriculture under a conventional tillage system with winter fallow. Phytosociological evaluations of all treatments were carried out 75 DAE of the oilseed crops, and the diversity indexes of Margalef, Menhinick, Simpson, and Shannon-Weiner were determined. Areas were also grouped by cluster analysis based on UPGMA applied at Jaccard's similarity matrix. Among the treatments with winter coverage, radish was the most efficient crop in suppressing the occurrence of weed species. The area with conventional tillage agriculture and winter fallow allowed for a higher occurrence of troublesome weeds. On the other hand, the area under fallow showed the highest absolute level of infestation. Overall, oilseed crops in the winter contribute to lower levels of infestation by weed species in these areas.